Evaluación de los puntos críticos de contaminación sonora en la ciudad de Moyobamba - Leiva Vásquez, Lis Del Carmen (2014)
The present research project entitled "ASSESSMENT OF THE CRITICAL POINTS OF SOUND POLLUTION IN MOYOBAMBA CITY, SAN MARTIN 2014" was developed in the Moyobamba city, taking aims to identify the critica! points of noise pollution in the Moyobamba city. The study consisted of 11-monitor pre certain points in Moyobamba city, during 4 months. The monitoring points were located in areas of special protection, residential, commercial and industrial area of Moyobamba city, with the achievement to reach the following conclusions: -/ The average noise levels in the monitoring points of Moyobamba city range during day between 63.8 and 74_3 dB(A) range of decibels and at night in the range of 59.2 and 70.5 dB(A) decibels. The high ranges observad in the Point of Monitoring N o 0004, whose maximum value is 104.78 dB (A) in the night day and the mínimum is of 44.68 dB (A) in the diurna! day. The same ones that there are influenced by the commercial activities and public transport (motokar traffic) which develop during the diurnal schedule and 1 or the night schedule. Well it are influenced by the sales promotion or activities through loudspeakers or over and the music levels emitted by leisure facilities and fun were the commercial activities that impacted on the high noise levels identified. -/ Analysis of the noise values obtained, allowed us to identify the critica! points in Moyobamba city, the same that were determinad with reference to the regulations in force - by areas - of this it was concluded the foliowing: • lt is considerad that the 100 per cent (4 points analyzed), 90.9 % (11 points analyzed), 54.54 % (11 points analyzed) of the monitoring points analyzed for the special protection area, area residence and for the shopping area respective! y, as critica! beca use they exceed the maximum allowable limits set forth in the regulations in force in the daytime, in the case of the industrial zone in none of the points exceeds the LMP. • lt is considerad that the 100 per cent (4 points analyzed), 100% (11 points analyzed), 90.9 % (11 points analyzed) and 63.63 % (11 points analyzed) the monitoring points analyzed for the special protection area, residential area, commercial area and to the industrial zone respectively as critica! because they exceed the maximum allowable limits set forth in the regulations in force in the evening hours . ./ lt was achieved to elaborate two maps: INVERSE WEIGHTING MAP OF DIURNAL ANO NIGHT NOISE. Key words: sound pollution; critica! points.